Efektivitas Cognitive Behavioral Therapy (CBT) pada Konteks Trauma Perang Timur Tengah - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
This study evaluates the effectiveness of culturally adapted Cognitive Behavioral Therapy (CBT) in the treatment of war trauma in the Middle East through an analysis of 47 studies involving a total of 4,628 participants from 2000 to 2024. The findings indicate that culturally informed CBT interventions have produced a significant therapeutic effect (g = 0.82, 95% CI [0.71, 0.93], p < .001) with a moderate level of heterogeneity (I² = 68%). Furthermore, culturally adapted CBT has been shown to reduce symptoms of Post-Traumatic Stress Disorder (PTSD) by 43.2% (d = 1.24, p < .001), anxiety by 38.7% (d = 0.96, p < .001), and depression by 35.9% (d = 0.88, p < .001). Additionally, moderator analysis revealed that the effectiveness of CBT significantly increases when the therapy integrates traditional healing practices (β = 0.34, p < .01) and involves family members in the intervention process (β = 0.29, p < .01). These findings expand upon previous research by Almoshmosh et al. (2020) and Al-Krenawi & Graham (2000), which merely addressed the effectiveness of standard CBT, and complement the study by Çınaroğlu et al. (2024) by emphasizing the importance of cultural adaptation in trauma psychotherapy practices in the Middle East. Furthermore, the main novelty of this research lies in identifying specific cultural components that enhance the effectiveness of CBT in the Middle East, including the integration of religious values (β = 0.31, p < .01) and the use of local cultural narratives in therapeutic approaches (β = 0.27, p < .01). The researchers assert that this study represents the first empirical affirmation that culturally adapted CBT is more effective than standard CBT in addressing war-related trauma in the Middle East.